PENDAYAGUNAAN TENAGA PENDIDIK DALAM MENINGKATKAN MUTU PENDIDIKAN - Aji Baksin (UNIVERSITAS BENGKULU, 2015)
The purpose of this research are description the plan of efficiency educator, realization of efficiency educator, evaluation of efficiency educator and description the support and hindrance factor of efficiency educator in increase the quality of educator at senior high school Ma’arif Lubuklinggau. The method this research are observation, interview and documentation with the subject of research are the principle, teacher and educator at senior high school Ma’arif Lubuklinggau. The result of research based on observation and interview that (1) the principle has done his task and his function with the founding toward educator at senior high school Ma’arif Lubuklinggau so occur increase the quality of education.Key words: efficiency, educator, the quality of educator.